Survival Benefit of En Bloc Transplantation of Small Pediatric Kidneys in Children. Issue 11 (November 2020) - Kizilbash, Sarah J.; Evans, Michael D.; Chinnakotla, Srinath; Chavers, Blanche M.
Abstract : Background: En bloc transplantation of small pediatric kidneys in children may help expand the existing deceased donor pool; however, studies examining the long-term outcomes of en bloc transplantation in children are few. Methods: We used the Scientific Registry of Transplant Recipients to identify 149 pediatric en bloc recipients transplanted from October 1, 1987 to December 31, 2017. We used propensity scores to match 148 en bloc with 581 non-en bloc deceased donor recipients (matching variables: transplant age, gender, race, pretransplant dialysis, transplant center, and year). We evaluated patient and graft survival using Kaplan-Meier and Fleming-Harrington weighted log-rank test and examined survival benefit of en bloc transplantation versus remaining on the waiting list using the sequential Cox approach. We divided the study period into three 10-y intervals to assess the effect of era on outcomes. Results: Compared with non-en bloc recipients, en bloc recipients had lower 1-y graft survival (78.9% versus 88.9%; P = 0.007); however, when stratified by transplant era, lower 1-y survival was only observed in the oldest era (1987–1997). En bloc recipients had superior 10-y patient (89.0% versus 80.4%; P = 0.04) and graft survival (51.6% versus 39.9%; P = 0.04) compared with non-en bloc recipients. After multivariate adjustment, en bloc transplantation was associated with superior patient survival compared with remaining on the waiting list (adjusted hazard ratio: 0.58; 95% confidence interval: 0.36-0.95; P = 0.03). Conclusions: En bloc transplantation of small pediatric kidneys in children is associated with superior long-term patient and graft survival. The increased risk of 1-y graft loss among en bloc recipients only appeared in the oldest era.